2004
DOI: 10.1108/14777830410523099
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of facilities and their environmental performance

Abstract: Improving indoor environmental conditions and, thus, health standards will have a direct impact on the performance of the employees and, thus, organisations and on the wealth of the community. The indoor air quality, lighting, ergonomics, acoustics and health complaints scales are widely used to determine building performance levels. The research model was tested using responses from 362 employees in 25 diverse hospitals. The results indicate that building comfort level assessments play a critical role in infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 8 publications
2
19
0
8
Order By: Relevance
“…Although both adults and children are affected by the poor IEQ, young children are arguably of greater concern due to their susceptible immune systems (Montzamani et al, 2012;Zhang et al, 2006;Mendell and Heath, 2004). Among the different physical discomforts derived from poor IEQ, fatigue condition and sick building syndrome have been reported as the most common discomforts in buildings (Musa et al, 2012;Mendell and Heath, 2004;Tarcan and Varol, 2004;Frontczak and Wargocki, 2011;Issa et al, 2011). Studies also show that the health impairment of students and teachers resulting from poor IEQ could influence students' performance, behavior, and productivity (Mendell and Heath, 2004;Treputtharata and Tayiam, 2014;Lee et al, 2012;Earthman, 2004;Huang et al, 2012;Passero andZannin, 2012 andHawes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although both adults and children are affected by the poor IEQ, young children are arguably of greater concern due to their susceptible immune systems (Montzamani et al, 2012;Zhang et al, 2006;Mendell and Heath, 2004). Among the different physical discomforts derived from poor IEQ, fatigue condition and sick building syndrome have been reported as the most common discomforts in buildings (Musa et al, 2012;Mendell and Heath, 2004;Tarcan and Varol, 2004;Frontczak and Wargocki, 2011;Issa et al, 2011). Studies also show that the health impairment of students and teachers resulting from poor IEQ could influence students' performance, behavior, and productivity (Mendell and Heath, 2004;Treputtharata and Tayiam, 2014;Lee et al, 2012;Earthman, 2004;Huang et al, 2012;Passero andZannin, 2012 andHawes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These health problems could lead to organizational symptoms such as job dissatisfaction, absenteeism, and poor work quality. Irritated, sore eyes and throat, hoarseness, stuffy congested nose, excessive mental fatigue, headaches and unusual tiredness were all signs of negative workplace environmental conditions (Tarcan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tarcan and Varol [16] in their study involving 375 individuals working in 25 hospitals found that indoor air quality is highly predictive of SBS and building general sufficiency level. Abdel-Hamid [3] found that poor ventilation and high temperature are predictive of SBS among office workers.…”
Section: Indoor Work Environment and Sick Building Syndromementioning
confidence: 99%